Investigation of the optimal rabbit model for aortic valve stenosis. (25th November 2020) - Anousakis-Vlachochristou, N; Katsa, M; Panara, A; Varela, A; Kyriakidou, M; Kapelouzou, A; Nitsa, A; Galiatsatos, N; Toutouza, M; Anastassopoulou, I; Thomaidis, N; Anagnostopoulos, C; et al.
Abstract: Background/Purpose: Anatomically, hemodynamically relevant and validated animal models for aortic valve stenosis are of great need. Drolet rabbit model with tricuspid anatomy produced conflicting results for unclear reasons. We hypothesized that limitations concentrate in the regimen administration. We sought to evaluate multiple doses, ways of administration and time periods. Methods: We included New Zealand rabbits in 4 groups: Group A (Drolet): was fed with normal chaw (nc)+0.5% cholesterol (chol)+3500 IUs Vitamin D2/kg (VD2, ergocalciferol, Sigma) in water daily for 12 weeks (wks), Group B: nc+0.5%chol+3500 IUs/kg VD2 in oil incorporated in a bisquit daily for 8 wks, Group C: nc+0.5%chol+8750 IUs/kg VD2 in oil-biscuit for 8 wks, Group D: nc+0.5%chol+17500 IUs VD2 in oil-biscuit for 8 wks vs controls (fed only with nc). After 12 and 8 wks the rabbits were sacrificed. Aortic valve area (AVA) and mean gradient (meanGr) were assessed with echocardiography (Vivid 7, M3S transducer, GE) and serum obtained, at baseline and before sacrifice. VD2 levels were evaluated through Chemiluminescent Microparticle Immuno Assay (CMIA, Abbott) and liquid chromatography – tandem mass spectrometry (LC-APCI-MS/MS). Animals received i.v. 18F-NaF one hour before sacrifice and valve was ex-vivo imaged with microPET/CT (Mediso nanoScan). Aortic cusps were analyzed with Fourier-Transformed Infrared Spectroscopy (FT-IR, Nicolet 6700 spectrometer, OMNIC 7.3 software). Valves from surgical patients with severe stenosis served for comparison purposes. Results: In Group A at 12 wks AVA and meanGr remained unchanged but biomineralization was detected with FT-IR with vibrations in the region of 1800–800 cm –1 demonstrating the deposition of CaCO3 and non-hydroxyapatite Ca3(PO4)2 identical to human lesion. Calcification was detected on cusps with 18F-NaF. VD2 levels were out of upper detection range with CMIA due to cross reaction, whereas all samples measured through LC-MS/MS were below the detection limit of the method (<19, 1 ng/mL). Significant Assessment heterogeneity (RSD=27%) was observed on VD2 water regimen. In Group B, AVA changed from 0.5 cm 2 to 0.4 cm 2 and meanGr increased from 1.1 to 2.1 mmHg, p<0.05 and in Group C AVA: 0.5 cm 2 to 0.3 cm 2 and meanGr: 1 to 2.95 mmHg, p<0.05, while VD2 serum concentration were 511 ng/mL. In Group D animals die unexpectedly at 2 weeks, with autopsy revealing massive myocardial hypertrophy of the left ventricle (LVH) without compromise of the aortic valve. Conclusions: The modified diet produces aortic valve stenosis and biomineralization detectable with 18F-NaF, chemically identical to human lesion. Very high doses of Vitamin D2 directly produce LVH, possibly leading to arrythmiogenesis. The modified high-fat-vitamin D2 rabbit model proved suitable for translational research of aortic valve stenosis disease. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National and Kapodistrian University of Athens